(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: COPD is one of the most widespread noncommunicable diseases, and its incidence is on the rise in developing countries. Acute COPD exacerbation is linked to a higher financial burden on the health system, as well as a negative impact on patients’ health in terms of lost working days, functional capacity, and mortality. COPD exacerbation is characterized by a worsening of symptoms such as cough and dyspnea, as well as a considerable risk of type-II respiratory failure. An understanding of the symptoms and signs, as well as the causes linked to acute COPD exacerbation in our population, is thought to aid in the prevention of such exacerbations, reducing the burden on patients and the community. Aim: This study is meant to bring forth the clinical profile and variables related with acute exacerbation of COPD among our community, taking into account the specific symptoms preceding an exacerbation of COPD and the variety of factors associated with it in different parts of the world. This study characterizes the clinical signs and symptoms of COPD acute exacerbations, as well as investigates the involvement of a respiratory tract infection in COPD exacerbation establishing a relationship between smoking and COPD exacerbation. Method: This is a hospital-based cross-sectional observational study. The study was conducted at the Dhaka Medical College Hospital’s Department of Medicine (DMCH). A method of purposive sampling was applied. The study took place from November 2012 until June 2013. The sample size computed for this study is 75. Result: Age above 7th decade increases mortality risk by 2.32 times. Meanwhile, comorbidity, low BMI (<18.5 kg/m2), smoking and frequent acute exacerbation increases risk by 1.29 times, 1.16 times, 0.03 times and by 2.07 times respectively in patients having COPD. Conclusion: Chronic obstructive pulmonary disease (COPD) is more frequent in the 6th decade of life and is male predominant. Recovery period has been found longer in the presence of dyspnea or symptoms of a common cold at exacerbations onset, higher PaCO2 and lower pH has been found in the patients admitted in ICU. Low BMI, RTI, Smoking and Comorbidity are more frequent in patients with chronic obstructive pulmonary disease (COPD). Sir Salimullah Med Coll J 2022; 30: 161-167